Manajemen Talenta Berbasis Sistem Merit Bagi Generasi Muda ASN di Sektor Publik - Andriani Kumala, Sheila; Dwi Sukmawati, Indirani (Policy, Law and Political Research Center, 2025)
This study aims to examine and analyze merit-based talent management for Generation Y and Z in the public sector, and to propose a new conceptual model tailored to the characteristics of these generations. The research employs a qualitative approach through a literature review of relevant regulations particularly the Indonesian Ministry of Administrative and Bureaucratic Reform Regulation No. 3 of 2020 on Civil Service Talent Management and academic studies on talent management. The study expands the conventional four-stage talent management model (acquisition, development, retention, and placement) into six stages: planning, acquisition, development, performance management, engagement, and retention. The main conceptual contribution lies in the addition of three key stages: planning, as a strategic initial phase; development, which differentiates between individual and career development; and engagement, which emphasizes employees’ emotional involvement within the organization. This research offers a novel conceptual framework that is more adaptive to the dynamics of younger generations in the public sector and serves as a reference for reforming merit-based talent management policies.